PESagri: A novel payments for ecosystem services framework for targeted agrienvironmental policy - Rodríguez-Ortega T.; Bernués A.; Olaizola A.M. (Innovation for sustainability in sheep and goats, 2019)
Multifunctional farms and policy makers need to connect agricultural management with the delivery of ecosystem services (ES) to improve policy outcomes and satisfy social demands. Despite the increasing understanding of the complex causal relationships between agricultural practices, biophysical processes and ES delivery, the application of the ES framework to agrienvironmental policy remains very limited. In this context, we developed a reliable and flexible framework of Payments for Ecosystem Services (PES) for the implementation of targeted agrienvironmental measures at the farm level. The PES framework i) focuses on agricultural activity as the main driver of many ES such as biodiversity and landscape conservation; ii) links objectively the real practices at the farm with the provision of relevant ES; iii) uses expert knowledge that allows evaluating and comparing the multiple effects of agricultural practices on ES; iv) reflects the views of all stakeholders involved; and v) constitutes a generic and versatile framework that can be used in diverse agroecological and policy settings. The paper describes the structure and operation of the PES system that is implemented in Excel. We use the case of sheep and mixed sheep-crops systems in the Euro-Mediterranean basin to illustrate the results of the PES application with diverse environmental objectives; for example, a policy targeting the real preferences of society for ES provision by Spanish sheep systems (i.e. wildfire prevention 53.2% of total importance, provision of quality products linked to the territory 20.2%, conservation of biodiversity 18.4%, and conservation of agricultural landscape 8.2%).
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)